2010
DOI: 10.1007/s00038-010-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional socioeconomic indicators and ethnicity as predictors of regional infant mortality rate in Slovakia

Abstract: ObjectiveExploring the associations of regional differences in infant mortality with selected socioeconomic indicators and ethnicity could offer important clues for designing public health policy measures.MethodsData included perinatal and infant mortality in the 79 districts of the Slovak population in 2004. Linear regression was used to analyse the contribution of education, unemployment, income and proportion of Roma population on regional differences in perinatal and infant mortality rates.ResultsAll the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
1
34
1
3
Order By: Relevance
“…Kolvek et al (2012) showed a higher risk of end stage renal disease to be associated with Roma ethnicity, which might be partially explained by a higher occurence of diabetic nephropathy. Rosicova et al (2011) found Roma ethnicity as a predictor of regional infant mortality rate in Slovakia. This is likely to contribute to the poorer CHD outcomes among Roma (Ginter 1998;McKee 1997;Hajioff and McKee 2000), but evidence on this is lacking.…”
Section: Introductionmentioning
confidence: 94%
“…Kolvek et al (2012) showed a higher risk of end stage renal disease to be associated with Roma ethnicity, which might be partially explained by a higher occurence of diabetic nephropathy. Rosicova et al (2011) found Roma ethnicity as a predictor of regional infant mortality rate in Slovakia. This is likely to contribute to the poorer CHD outcomes among Roma (Ginter 1998;McKee 1997;Hajioff and McKee 2000), but evidence on this is lacking.…”
Section: Introductionmentioning
confidence: 94%
“…Studies conducted globally suggest that , mother's exposure to mass media, use of clean cooking fuel, access to a toilet facility, improved/safe drinking water facility, mother's religion and ethnicity, income of the household, birth order, mother's age at birth, birth intervals, availability of professional antenatal and delivery care, full immunization of children, mother's education, and urban-rural residence are all correlates of infant and child mortality [6,7,8,9]. With regards to the mother's educational level, studies have found an inverse relationship between highest level of education of mother and child survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] This may be due to the socioeconomic (SE) characteristics of both these residents 7 and of the areas where they live. 2,[8][9][10] Area-level SE differences in Western European (WE) 6,9,[11][12][13][14][15][16] and Central European (CE) countries [17][18][19][20] are well documented. Studies on urban-level effects on health outcomes are mostly performed in the United States, 21 Canada, 4 the United Kingdom 22 and WE countries.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Slovakia, to our knowledge, the only available study is that of Rosicova et al, [18][19][20] who found in a series of ecological studies that SE and ethnic indicators predicted the standardized mortality rate and alcohol-related mortality rate among districts in Slovakia in men aged 20-64 years, as well as perinatal and infant mortality. Regarding the Netherlands, the effect of areas on health have been studied much more intensively.…”
Section: Introductionmentioning
confidence: 99%